(untitled) (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2025)
The article analyzes the changes promoted by Law No. 13,467/2017 in Collective Labor Law, focusing on the inclusion of articles 611-A and 611-B and the new wording of articles 614 and 620 of the CLT. The author discusses the prevalence of the negotiated over the legislated, the prohibition of the ultra-activity of collective norms, and the supremacy of collective agreements over collective conventions. It concludes that such changes, although declared constitutional by the STF (Theme 1046), tend to weaken the union struggle and worker protection. (Received: June 2025 | Accepted: September 2025).